A rapid tick exposure test for monitoring acaricide resistance in Rhipicephalus sanguineus sensu lato ticks on dogs - Frans Jongejan; Laura Berger; Elias Papadopoulos; José Reck; Priscila Teixeira Ferreira; Fabio Barbour Scott; Barbara Rauta de Avelar; Brena Gava Guimarães; Thais Ribeiro Correia; Iris Hulsebos; Alita Petersen; Guilherme Klafke (Parasites & Vectors, 2024)
Abstract Background Brown dog ticks (Rhipicephalus sanguineus sensu lato) are vectors of pathogens adversely affecting the health of dogs in many regions of the world. The three-host life cycle of R. sanguineus s.l., with all stages feeding on dogs, can lead to an uncontrolled build-up of large tick populations if not controlled by acaricides. However, frequent tick control on dogs using acaricides has led to the emergence of resistance to permethrin and fipronil. Currently, the larval packet test (LPT) is the standard tick resistance test, which is laborious, requires laboratory facilities, and takes at least 6 weeks before larvae derived from engorged female ticks can be tested. Our novel approach is to expose semi-engorged adult ticks to acaricides immediately after removing them from dogs, obtaining results within 24 h. Methods Adult ticks from three laboratory colonies of R. sanguineus s.l. were tested in RaTexT®, a rapid tick exposure test in which ticks were confined to small compartments and exposed to an acaricide-impregnated, specially designed matrix. Resistance was confirmed by testing larvae derived from the same laboratory colonies using the LPT. RaTexT® was also used to determine the susceptibility of R. sanguineus acaricides in dog shelters. Results RaTexT® detected resistance to permethrin in adult R. sanguineus s.l. ticks from two Brazilian laboratory colonies compared to a susceptible laboratory strain originating in Greece. Resistance was confirmed by LPT testing of larvae from the same colonies with resistance factors between 2.2 and 3.1. All laboratory strains were susceptible to fipronil. A suspected case of fipronil resistance at a dog shelter in Caxias do Sul, Brazil, was resolved within 24 h by testing adult ticks in RaTexT® and could be attributed to improper treatment. Conclusions RaTexT® is a valuable tool for monitoring the development of resistance to synthetic pyrethroids or phenylpyrazoles in tick-infested dogs. Graphical Abstract